Concepts and procedures for the Development of improved Vertisol technology Development in Ethiopia - Asamenew, G.; Mohamed-Saleem, M.A. (IBSRAM, 1992)
Presents the concept and procedure followed to develop an appropriate technology to increase productivity on Vertisols (heavy clay soils) in Ethiopia. Describes the Vertisol farming systems in the Ethiopian highlands and discusses the on-farm technology validation process. Examines yields of major crops from traditional farming at Dogollo and Inewari. Lists number of farmers that participated in the on-farm BBF broad beds and furrows) technology research, 1986-1990. Presents a model showing changes that may result from use of improved Vertisol technology, an overview of procedures for Vertisol technology Development and transfer of data and sequence of evaluation activities in on-farm BBF technology verification. Also assesses the effects of improved Vertisol management on wheat grain and straw yields and economic returns at Dogollo.